PERTIMBANGAN KEADILAN PERSPEKTIF ADAT JAWA TERHADAP PEMBAGIAN PERAN SUAMI ISTRI: The Division of Roles of Husband and Wife in Javanese Society: A Justice Perspective - Arifin, Mochammad; Rohman, Miftakhul; Slamet, Slamet (ISTIDLAL, 2024)
Family is one of the forms that every married person dreams of. Many families are harmonious because they have complete members including father, mother and children. Apart from that, economically they feel sufficient so they look happy. However, not everyone experiences this, the more children and assets they have, the more problems they have after one of their family members dies, namely the issue of inheritance rights. Inheritance is often a problem that involves many parties to resolve it, such as law enforcement and custom. Therefore, this research will discuss the role of husband and wife in dividing inheritance rights according to Javanese custom. The aim of this research is to describe the distribution of family roles in tribal couples. Java. This research uses qualitative phenomenological methods. The subjects of this research were six married couples of Javanese descent who lived in Surakarta. Data was collected using semi-structured interview techniques. The data analysis method used was descriptive analysis. The research results showed that: 4,444 (1) couples shared roles in three areas of decision making, family financial management and child care; (2) the process of implementing these roles is flexible; (3) the husband plays more of a role in decision making, while the wife takes over financial management and childcare. Efforts to maintain harmonious relationships within the couple remain the main priority in carrying out this role. It can be concluded that the teachings of harmony are still the guidelines for husband and wife relationships in Javanese families.